Revolutionizing Drama Education: A Journey through Virtual Simulation Technology - Hu, Yaxin; Shu, Jack; He, Mengtian (Transactions on Social Science, Education and Humanities Research, 2024)
In this paper, we deeply discuss the practical application of virtual simulation technology in the field of drama teaching. First, we analyze how virtual simulation technology can improve the efficiency of drama teaching through simulation, intelligent interaction and personalized learning. Subsequently, we detail how virtual simulation technology can help educators create more innovative and immersive drama courses. Finally, we delve into the challenges that may arise when integrating virtual simulation technology into drama teaching and propose solutions to overcome these obstacles in order to optimize the effectiveness of drama teaching. The purpose of this paper is to provide educators with a fresh perspective to better understand and utilize the potential of virtual simulation technology in drama teaching and learning.